MODIFIKASI DONGKRAK BOTOL DAN TREKER UNTUK MELEPAS BEARING MOTOR LISTRIK - Marjuki, Ismael; Helanianto, Helanianto; Polonia, Betti Ses Eka (Pengelola Jurnal Politeknik Negeri Ketapang, 2022)
This research modifies the bottle jack to remove the electric motor bearing of a water pump with a jackcapacity of 2 tons. Bottle jacks are generally used to lift vehicles such as cars. The bottle jack can be modified sothat it can be used as a bearing removal device. In general, the way to remove the bearing is still manual, namelyby hitting it. The purpose of making this tool is to make it easier to remove the water pump electric motor bearing.The working principle of this removal tool is to use hydraulic power as the driving force. Pushers from the bottomup on the water pump dynamo shaft and a tracker as a means of holding the bearing. The bearing holder is neededso that the bearing can be separated from the water pump dynamo shaft. The specifications of the tool are that ithas a height of 16 - 27 cm. The width of the tool is 6 cm and the maximum pressure capacity of the bottle jack is2 tons. The trial results of the bottle jack modification tool to remove the water pump electric motor bearingsobtained an average time of 45 seconds.